Relationship between mentoring program characteristics, self-efficacy and mentee outcomes:a study of Malaysian institutions of higher learning in Sarawak - Kho, Michael Khian Jui. (Universiti Malaysia Sarawak (UNIMAS), 2011)
Training and development program literatures draw attention to two salient characteristics of mentoring progams: communication and support. The ability of mentors to properly implement comfortable communication style (e.g., communication openness) and provide adequate support (i.e., encouragement) may have a significant impact on mentee outcomes (i.e., psychosocialand academic performance), Research in this area reveals the effects of mentoring program chaacteristics on mentee outcomes to be indirectly affected self-efficacy. Though the relationship is interesting in nature, little is known on the mediating effect of self-efficacy in mentoring program. Thus, it motivates the researcher to further explore this issue.